The Word in the World: A Study on the use of the Scriptures of the World Religions in Christian Worship - Manickam, Thomas (Journal of Dharma, 1996)
Saju Chackalackal, The Word in the World : A Study on the use of the Scriptures of the World Religions in Christian Worship, Vidya Vanam publications, Bangalore-560029, India, (1 995), pp. xvii+110. Rs. 60.00 ( 9.00.)